2010
DOI: 10.1038/nature09347
|View full text |Cite
|
Sign up to set email alerts
|

Notch and EGFR pathway interaction regulates neural stem cell number and self-renewal

Abstract: Specialized cellular microenvironments, or “niches,” modulate stem cell properties, including cell number, self-renewal and fate decisions1,2. In the adult brain, niches that maintain a source of neural stem cells (NSCs) and neural progenitor cells (NPCs) are the subventricular zone (SVZ) of the lateral ventricle and the dentate gyrus of the hippocampus3–5. The size of the NSC population of the SVZ at any time is the result of several ongoing processes, including self-renewal, cell differentiation, and cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
395
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(414 citation statements)
references
References 38 publications
14
395
0
5
Order By: Relevance
“…In the adult brain, EGFR has been shown to play a critical role in the regulation of the neurogenic niches, found in the SVZ of the forebrain and the subgranular zone of the hippocampus 8 9 10, where activation of stem cells appears to correlate with the acquisition of EGFR expression 9. Overexpression of the EGFR in neural precursor cells has been shown to result in reduced neural stem cell proliferation and self‐renewal in the SVZ 11, illustrating a critical role of EGFR signaling not only in neural stem cell maintenance but also in astrocyte differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In the adult brain, EGFR has been shown to play a critical role in the regulation of the neurogenic niches, found in the SVZ of the forebrain and the subgranular zone of the hippocampus 8 9 10, where activation of stem cells appears to correlate with the acquisition of EGFR expression 9. Overexpression of the EGFR in neural precursor cells has been shown to result in reduced neural stem cell proliferation and self‐renewal in the SVZ 11, illustrating a critical role of EGFR signaling not only in neural stem cell maintenance but also in astrocyte differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, differentiated adult mesenchymal stem cells show pro-liferation capacity, but it has been suggested that the therapeutic potential of stem cells, due to bioactive growth factor secretion and stimulation of neoangiogenesis, may be limited by their senes-cence, or biological aging, and by the age of the donor [8]. Recent reports indicate that aging is linked to a decline in the number of stem cells found in bone marrow aspirate [9] and of their potential to proliferate and differentiate [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Notch signalling seems to influ-ence important roles in many types of stem cells [8]. Adult stem cells have limited selfrenewal and proliferative potential, which decreases with the advancing age of the organism [24].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it contains the mitogenic receptor tyrosine kinase Egfr that promotes neurogenesis and supports hippocampal LTP formation by influencing NMDAreceptor trafficking (Aguirre, Rubio, and Gallo, 2010;Tang, Ye, Du, Qiu, Lv, Yang, and Luo, 2015).…”
Section: Discussionmentioning
confidence: 99%